C5aR1 regulates migration of suppressive myeloid cells required for costimulatory blockade‐induced murine allograft survival. Issue 3 (17th September 2018) - Llaudo, Ines; Fribourg, Miguel; Medof, M. Edward; Conde, Patricia; Ochando, Jordi; Heeger, Peter S.
Abstract : Costimulatory blockade‐induced murine cardiac allograft survival requires intragraft accumulation of CD11b + Ly6C lo Ly6G − regulatory myeloid cells (Mregs) that expand regulatory T cells (Tregs) and suppress effector T cells (Teffs). We previously showed that C5a receptor (C5aR1) signaling on T cells activates Teffs and inhibits Tregs, but whether and/or how C5aR1 affects Mregs required for transplant survival is unknown. Although BALB/c hearts survived >60 days in anti‐CD154 (MR1)‐treated or cytotoxic T‐lymphocyte associated protein 4 (CTLA4)‐Ig–treated wild‐type (WT) recipients, they were rejected at ~30 days in MR1‐treated or CTLA4‐Ig–treated recipients selectively deficient in C5aR1 restricted to myeloid cells ( C5ar1 fl/fl xLysM‐Cre ). This accelerated rejection was associated with ~2‐fold more donor‐reactive T cells and ~40% less expansion of donor‐reactive Tregs. Analysis of graft‐infiltrating mononuclear cells on posttransplant day 6 revealed fewer Ly6C lo monocytes in C5ar1 fl/fl xLysM‐Cre recipients. Expression profiling of intragraft Ly6C lo monocytes showed that C5aR1 deficiency downregulated genes related to migration/locomotion without changes in genes associated with suppressive function. Cotransfer of C5ar1 fl/fl and C5ar1 fl/fl xLysM‐Cre myeloid cells into MR1‐treated allograft recipients resulted in less accumulation of C5ar1 − / − cells within the allografts, and in vitro assays confirmed that Ly6C hi myeloid cells migrate to C5a/C5aR1‐initiated signals. Together, our results newly link myeloid cell–expressed C5aR1 to intragraft accumulation of myeloid cells required for prolongation of heart transplant survival induced by costimulatory blockade. Abstract : The investigators use conditional knockout mice to demonstrate that monocyte expression of C5a receptor 1 provides important chemoattractant signals that attract regulatory myeloid cells to cardiac allografts and is required for prolonged murine cardiac allograft survival induced by costimulatory blockade. See Riquelme et al's commentary on page 619 .